STUDENTS’ SURFACE STRATEGY TAXONOMY ERRORS IN NARRATING A STORY: A MORPHO-SYNTACTICAL VIEW - Fahmi Hidayat; Ninuk Krismanti (STKIP Persada Khatulistiwa Sintang, 2022)
This study was set to reveal students’errors in speaking. The errors were limitted to surface strategy taxonomy errors with the focus of morphological and syntactical errors. The study was carried out under a mixed-method design where both quantitative and qualitative data were both needed. 33 students of ELESP Lambung Mangkurat University participated in this study. The participants were asked to orally create a story based on sequence pictures given to them. The recordings of students’ stories were then transcribed and analyzed. The results of the study suggested that 249 errors from different categories occured in students’ stories. The most prominent errors were found in Omission and Misinformation categories. The errors suggested students’ lack of understanding in English grammatical rules. However, despite the errors, students’ stories were still easy to comprehend. Keywords: errors; speaking; surface strategy taxonomy; morphology; syntax